PROPOSTA DE ATENÇAO AO PORTADOR DE DOENÇA PULMONAR OBSTRUTIVA CRÔNICA NA REDE DE ATENÇAO BÁSICA À SAÚDE - EICKHOFF, HELOISA M.; LUZ, JOSEANE M. D.; RIBEIRO, RAFAELA L. (Salão do Conhecimento, 2013)
Resumo